Effects of curcumin on NF‐κB, AP‐1, and Wnt/β‐catenin signaling pathway in hepatitis B virus infection. Issue 10 (19th June 2018) - Hesari, AmirReza; Ghasemi, Faezeh; Salarinia, Reza; Biglari, Hamed; Tabar Molla Hassan, Agheel; Abdoli, Vali; Mirzaei, Hamed
Abstract: Curcumin is a yellow‐orange powder derived from the Curcuma longa plant. Curcumin has been used extensively in traditional medicine for centuries. This component is non‐toxic and shown different therapeutic properties such as anti‐inflammatory, anti‐cancer, antiviral, anti‐bacterial, anti‐fungal, anti‐parasites, and anti‐oxidant. Hepatitis B virus (HBV) is a small DNA member of the genus Orthohepadnavirus (Hepadnaviridae family) which is a highly contagious blood‐borne viral pathogen. HBV infection is a major public health problem with 2 billion people infected throughout the world and 350 million suffering from chronic HBV infection. Increasing evidence indicated that curcumin as a natural product could be employed in the treatment of HBV patients. It has been showed that curcumin exerts its therapeutic effects on HBV patients via targeting a variety of cellular and molecular pathways such as Wnt/β‐catenin, Ap1, STAT3, MAPK, and NF‐κB signaling. Here, we summarized the therapeutic effects of curcumin on patients who infected with HBV. Moreover, we highlighted main signaling pathways (eg, NF‐κB, AP1, and Wnt/β‐catenin signaling) which affected by curcumin in HBV infections. Abstract : Curcumin is a yellow‐orange powder derived from the Curcuma longa plant. Curcumin has been used extensively in traditional medicine for centuries. Curcumin is nontoxic and shown different therapeutic properties including anti‐inflammatory, ‐cancer, ‐viral, ‐bacterial, ‐fungal, ‐parasites, ‐oxidant, analgesic, and antiseptic activities. Hepatitis B virus (HBV) is a small DNA member of the genus Ortho hepadnavirus (Hepadnaviridae family) which is a highly contagious blood borne viral pathogen. HBV infection is a major public health problem with 2 billion people infected throughout the world and 350 million suffering from chronic HBV infection. In this review, we focus on recent studies highlighting the role of curcumin in Hepatitis B virus infection and their potential clinical applications in NF‐κB, AP1, and Wnt/β‐catenin signaling as a target for prevention and therapy.